The Impact of Interactive Reading Using Local Folktales Stories in Supporting Students’ Vocabulary Achievement in Indonesian EFL Learners - Ismail, Ismail; Samad, Ita Sarmita; Masnur, Masnur (Majesty Journal, 2019)
This study aimed to investigate the impact of interactive reading using local folktale stories on the vocabulary achievement of Indonesian EFL learners and to examine students’ attitudes toward the use of folktales in vocabulary instruction. The study employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 30 eleventh-grade students of SMA Muhammadiyah Kalosi, Enrekang, in the 2015/2016 academic year. Data were collected through vocabulary tests and a questionnaire. The tests were administered as a diagnostic test, Cycle I test, and Cycle II test to measure students’ vocabulary development. The findings showed a substantial improvement in students’ vocabulary achievement across the cycles. The mean score increased from 55.07 in the diagnostic test to 65.36 in Cycle I and reached 82.21 in Cycle II. These results indicate that interactive reading using local folktales effectively improved students’ vocabulary mastery. In addition, the questionnaire results revealed that students responded positively to the use of folktales, particularly in terms of enjoyment, cultural relevance, meaningful input, and vocabulary practice. The study concludes that local folktales provide authentic and engaging reading materials that not only enrich vocabulary learning but also foster positive attitudes toward English learning.